2011
DOI: 10.1002/marc.201100012
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Thin Film Phase Behaviour of Functional Rod‐Coil Block Copolymers Based on Poly(para‐phenylenevinylene) and Poly(lactic acid)

Abstract: We report the synthesis of a series of block copolymers consisting of a rod-like semiconducting poly(2,5-di(2'-ethylhexyloxy)-1,4-phenylenevinylene) (DEH-PPV) block and a flexible poly(lactic acid) (PLA) block that can be selectively degraded under mild conditions. Such selectively degradable block copolymers are designed as self-assembling templates for bulk heterojunction donor-acceptor layers in organic solar cells. A lamellar microphase-separated domain structure was identified for block copolymers with PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…On the basis of our knowledge, there has been no previous publication on the synthesis of a PLA‐NR diblock copolymer. The PLA‐based diblock copolymers have included PLA‐poly(ethylene glycol), PLA‐poly(ethylene oxide), PLA‐PS, and PLA‐poly(para‐phenylenevinylene) . NR has been chemically modified to obtain a hydroxyl terminated liquid rubber (a hydroxyl telechelic natural rubber, HTNR).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of our knowledge, there has been no previous publication on the synthesis of a PLA‐NR diblock copolymer. The PLA‐based diblock copolymers have included PLA‐poly(ethylene glycol), PLA‐poly(ethylene oxide), PLA‐PS, and PLA‐poly(para‐phenylenevinylene) . NR has been chemically modified to obtain a hydroxyl terminated liquid rubber (a hydroxyl telechelic natural rubber, HTNR).…”
Section: Introductionmentioning
confidence: 99%
“…The homopolymers and assemblies are further evaluated using fluorescence spectroscopy. Although the complementary helices and coils do not exhibit fluorescence, the emission properties of PPV homopolymers and covalent block copolymers, as well as their aggregation-influenced properties are well documented. ,, The hetero­telechelic PPV homopolymers exhibit emission maxima at 520 nm with a broad shoulder at 560 nm (Figure S-33). Both ABC triblock copolymers exhibit mainly relative changes in intensity compared to their parent PPV polymers.…”
Section: Resultsmentioning
confidence: 99%
“…Essential to this design is the development of a new functional initiator based upon Grubbs II; we realize this through an iterative cross-metathesis–ring-opening metathesis polymerization (CM-ROMP) strategy that installs an α-chain end upon the PPV. We choose PPV scaffolds for multiple reasons: (i) conjugated polymer frameworks serve as hosts for a variety of applications, ranging from electronics to sensing; (ii) homopolymers and block copolymers featuring PPVs are well-studied in the context of optical properties and molecular structures; and (iii) spectroscopic methodologies that can be used to explicitly investigate conjugated polymer folding motifs have recently emerged. ,, …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, Müllen and co‐workers demonstrated that end‐functionalized (hydroxymethyl)polyfluorene acts as an initiator in an anionic polymerization of oxirane to give a polyethylene glycol‐appended rod coil, featuring an oligofluorene block containing 2–6 repeat units 6. Very recently Ludwigs and co‐workers,7 starting from hydroxymethyl‐substituted poly[2,5‐di(2′‐ethylhexyloxy)‐1,4‐phenylene‐vinylene], attached a flexible poly(lactic acid) block to give rod coils with attractive mesoscopic lamellar structures as evidenced by atomic force microscopy (AFM) and transmission electron microscopy (TEM). Overall though, the synthesis of rod‐coil block copolymers is not trivial.…”
Section: Introductionmentioning
confidence: 99%